Formes de corrosion dans l’anorthosite sur le rivage est du lac Saint-Jean, - Dionne, Jean-Claude (Cahiers de géographie du Québec)

(untitled) (Département de géographie de l'Université Laval, 1972)
Minor corrosion features in anorthosite occur on the rocky shore in the east and southeast part of the lake St-Jean, Québec. Corrosion pits, 5 to 10 cm in diameter and 4 to 8 cm deep, are numerous on glacially-polished and striated rock surface at the mean lake level. The nature of the weathering is obscure but it is believed that waves play an important role in carrying out detritus and then producing small pits.